Biomass conversion via ablative fast pyrolysis and hydroprocessing towards refinery integration: Industrially relevant scale validation. (15th January 2023) - Dimitriadis, Athanasios; Bergvall, Niklas; Johansson, Ann-Christine; Sandström, Linda; Bezergianni, Stella; Tourlakidis, Nikos; Meca, Luděk; Kukula, Pavel; Raymakers, Leonard
Graphical abstract: Highlights: Ablative fast-pyrolysis with fractional condensation validated via 1200 kg bio-oil. Slurry hydroprocessing enabled bio-oil stabilization. Stablized bio-oil hydrotreated to high quality bio-based intermediate (BioMates) 20 wt% mass yield and 32 wt% carbon yield from straw to BioMates. Abstract: Reducing the use of fossil fuels is an ongoing and important effort considering the environmental impact and depletion of fossil-based resources. The combination of ablative fast pyrolysis and hydroprocessing is explored as a pathway allowing bio-based intermediates (BioMates) integration in underlying petroleum refineries. The proposed technology is validated in industrially relevant scale, identifying pros and cons towards its commercialization. Straw from wheat, rye and barley was fed to ablative fast pyrolysis rendering Fast Pyrolysis Bio-Oil (FPBO) as the main product. The FPBO was stabilized via slurry hydroprocessing, rendering a stabilized FPBO (sFPBO) with 49 % reduced oxygen content, 71 % reduced carbonyl content and 49 % reduced Conradson carbon residue. Fixed bed catalytic hydroprocessing of sFPBO resulted in the production of BioMates, a high bio-content product to be co-fed in established refinery units. Compared to the starting biomass, BioMates has 83.6 wt% C content increase, 92.5 wt% O content decrease, 93.0 wt% water content decrease, while the overall technology has 20 wt% conversion yield (32 wt% carbon yield) from biomass to BioMates.